Torkad eller gastät lagrad spannmål till värphöns : en fallstudie - Olausson, Anders (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
The purpose with this study is to compare different systems of grain storage from a financial point of view. Grain that is supposed to be fed to laying hens. The systems that were compared were different airtight storage of grain and a system of conventional storage.